Analisis Strategi UMKM Jiwaku Ricebowl dalam Menghadapi Pandemi Covid -19 - Anindita Nurjihan Dwi T; Muhamad Rizal; Ria Arifianti; Asmaul Husna (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2021)
On March 10, 2020, the start of the Covid-19 pandemic caused an impact that was felt by several countries, even the government and society. One of the impacts that is felt is not only a health problem but also attacks the country's economy, for example MSMEs as the Micro, Small and Medium Enterprises sector are experiencing a severe impact due to the Covid-19 pandemic. Based on information processed by LIPI's P2E, the impact of tourism shrinkage on MSMEs engaged in the micro food and beverage business reached 27%. Meanwhile, the impact on small food and beverage businesses was 1.77% and medium enterprises was 0.07%. This research is intended to see where the Covid-19 pandemic has grown and how it impacts the economy in Indonesia, especially MSMEs. Afifuddin Suhaeli Kalla said that income from MSMEs has decreased by 70% since the Covid-19 pandemic and this decreased turnover was also felt by Jiwaku's business after the PSBB was implemented. government because the city of Bandung has been exposed to the virus. This research was conducted to identify what MSME players were doing in order to maintain their business during the Covid-19 Pandemic. This research aims to describe and describe what strategies MSME actors want to try in order to be able to continue to survive and become more responsive to changes in the business climate through a SWOT analysis. This research uses a descriptive qualitative research approach and SWOT analysis to digest and create a strategy formulation.